The phenolic content, antioxidant and cytotoxic activities of Origanum sipyleum from Turkey - Arzu Kaska (International Journal of Secondary Metabolite)
Origanum sipyleum is a medicinal plant species belonging to the genus Origanum and traditionally vegetative parts of this plant have been used as medicinal tea or food additives. The current study has been designed to examine the antioxidant, cytotoxic activities and total phenolic, flavonoid and tannin contents as well as the chemical composition of the ethanol extract of O. sipyleum. The antioxidant capacity of O. sipyleum was determined using six complementary methods, β-carotene/linoleic acid and phosphomolybdenum test systems, radical scavenging (ABTS and DPPH), metal chelating and reducing power assays. The phenolics were identified using HPLC. A brine shrimp (Artemia salina L.) lethality test was used for determining cytotoxic activity. The ethanol extract exhibited high DPPH free radical scavenging (DPPH, IC50:102.75 µg/mL), ABTS radical scavenging (ABTS, IC50:88.64 µg/mL), metal chelating (20.68 %) and reducing power capacity (0.51 mg/mL). The antioxidant activities of the O. sipyleum with β-carotene/Linoleic acid and phosphomolybdenum were calculated as 85.59 % and 62.95 µg/mg respectively. The phenolic contents of the ethanol extract were evaluated using HPLC and determined major phenolics: caffeic acid, epicatechin and 2,5 dihydroxybenzoic. Furthermore, to gether with cytotoxic activity (LC50, 327.414 µg/mL) O. sipyleum is also rich in total phenolic, flavonoid and tannin contents were 203.57 ± 4.62 mgGAE/g, 46.98 ± 0.34 mgQE/g and 34.55 ± 0.56 mgCE/g respectively. These results could provide addition information for the potential use of this medicinal plant as a food ingredient and as a natural antioxidant in the diet, as well as for the pharmaceutical industry.